Ruptured Ectopic Pregnancy with Levonorgestrel Implant : A Contraceptive Failure and Life-threatening Case - Efrany, Erics; Pratiwi, Ketut Mira Yoga; Adiguna Dira, I Gede Mahendra; Widiabdi Husada, I Made Oka; Hartono, Dianawati (Green Publisher Indonesia, 2025)
Levonorgestrel implant is the most used in Indonesia, it is free provided by BKKBN. Levonorgestrel implant provides 99.95% of effectiveness. However, it could not prevent pregnancy absolutely including ectopic pregnancy. Ectopic pregnancy is a life threatening condition that is oftenly ignored by the patient and sometimes misdiagnosed. The incidence of ectopic pregnancy is very low, particularly in implant contraceptive users. Despite this fact, little is known about mechanism of implant failure including its correlation to ectopic pregnancy, and studies are limited. This case report presented a levonorgestrel implant contraceptive failure result in ectopic pregnancy. A 21-years-old woman P1001 was provided with levonorgestrel implant seventh month before admission. Patient was presented to emergency department after suffering from severe lower abdominal pain. She was diagnosed with ruptured ectopic pregnancy and underwent exploratory laparotomy. Her ruptured right fallopian tube was ligated and partially removed. Histopathological examination supported the diagnosis, chorionic villi lined with syncytiotrophoblast and cytotrophoblast cells in right fallopian tube tissue were found. The levonorgestrel implant was removed and she was scheduled for next contraceptive counseling. This case report emphasizes the fact that low incidence of contraceptive implant failure, does not rule out the possibility of ectopic pregnancy. Several hypotheses have been proposed as the cause of ectopic pregnancy. Further research is necessary to determine definitive etiology in ectopic pregnancy with levonorgestrel implant contraceptive failure.